2020
DOI: 10.1016/j.celrep.2020.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Non-conventional Axonal Organelles Control TRPM8 Ion Channel Trafficking and Peripheral Cold Sensing

Abstract: Highlights d TRPM8 nerve trafficking depends on a non-conventional axonal secretory route d GBF1 and RAB6 interaction orchestrate axonal Golgi satellites in nerve fibers d Local disruption of axonal secretory organelles affects TRPM8 cold sensing in mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 73 publications
(115 reference statements)
0
19
0
Order By: Relevance
“…As a first approach, we used Ca 2+ -imaging, a non-invasive technique that avoids a potential disruption of cell-signaling pathways. HEK-293 cells stably expressing mTRPM8-myc channels (HEK-293-mTRPM8-myc) [ 52 ] were preincubated for 10 min at 37 °C with extracellular solution containing 1 µM of PMA, or with control solution ( Figure 1 ). To exclude the direct effects of PMA on TRPM8 channels, we also tested the effect of the biologically inactive analog 4α-PMA at the same concentration as the active compound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a first approach, we used Ca 2+ -imaging, a non-invasive technique that avoids a potential disruption of cell-signaling pathways. HEK-293 cells stably expressing mTRPM8-myc channels (HEK-293-mTRPM8-myc) [ 52 ] were preincubated for 10 min at 37 °C with extracellular solution containing 1 µM of PMA, or with control solution ( Figure 1 ). To exclude the direct effects of PMA on TRPM8 channels, we also tested the effect of the biologically inactive analog 4α-PMA at the same concentration as the active compound.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the TRPM8 channel travels to the plasma membrane of primary sensory neurons in atypical secretory vesicles with lysosomal-associated membrane protein 1 (LAMP1) and RAB7 molecular identity [ 63 ]. Recently, we also described a non-conventional trafficking mechanism involved in the recycling of TRPM8 channels to the plasma membrane in sensory fibers, with an important role in peripheral cold sensing [ 52 ]. Our present findings suggest that PKC could alter TRPM8 trafficking, as is the case for several ion channels and transporters [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an outstanding article shows the experimental evidence in vitro and in vivo on the regulation of TRPM8 trafficking by axonal organelles and its crucial role for the cold sensation and transduction in peripheral axons [114]. The authors demonstrated the implication of the ARF-GEF Golgi-specific brefeldin A-resistance factor 1 (GBF1) through the inhibition of GBF1 in axons of the sciatic nerve and corneal cold thermoreceptors in vivo.…”
Section: Trpm8 Distribution and Pathological Implicationmentioning
confidence: 99%
“…However, to date, Golgi structures have been identified in dendrites, and not in axons, in the central nervous system (CNS). In peripheral neurons, Golgi structures have been detected in both the dendrites (see below) and also recently in axons (Cornejo et al, 2020). Given the importance of the Golgi apparatus in post-translational modifications and anterograde transport of newly synthesized soluble and membrane proteins, more extensive studies have been carried out on the local secretory systems of dendrites compared with axons and, therefore, this review will focus on the local secretory organelles of dendrites.…”
Section: Introductionmentioning
confidence: 99%